Exploring How Environmental Accounting Impact Company Value: A Literature Review - Sianipar, Rifki Safutra; Lindrianasari; Syaipudin, Usep (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to adress the persistent environmental challenges in Indonesia, drawing attention to its low Environmental Performance Index (EPI) ranking and escalating carbon emissions. Despite governmental regulations, many corporations continue to inadequately comply. By using the literature review method, this research explores the contemporary understanding of corporate environmental practices and their impact on corporate value, revealing inconsistent findings. The study emphasizes the potential positive impact of effective environmental management, urging companies to view environmental costs as strategic investments in corporate reputation and long-term value. In conclusion, the study advocates for future research to delve into the intricate mechanisms through which environmental factors influence corporate value across industries, regions, and emerging trends in sustainable finance. This research aspires to provide valuable insights for refining policies and business practices in Indonesia, fostering sustainable development and environmental responsibility